PENGARUH KERELASIAN PEMASARAN DAN CITRA PERGURUAN TINGGI TERHADAP KEPERCAYAAN MAHASISWA PROGRAM DIPLOMA PADA SEKOLAH TINGGI ILMU ADMINISTRASI MANDALA INDONESIA DI JAKARTA - Nur Fitri Rahmawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
This study was conducted to determine relationship marketing , imagery STIAMI college diploma program in Jakarta , Diploma Student’s Trust and also determine how much influence of relationship marketing and college’s image partially and simultaneously on Diploma Student’s trust at STIAMI Jakarta.The population was STIAMI’s Diploma Student, amounting to 465 people and the researcher takes 117 among af the population be the sample. Each respondent was given a total of 32 questions using a Likert scale.The results of this study indicate that relationship marketing gives the positive influence and significant to the Diploma student’s trust, college’s image gives positive and significant impact to the Diploma student’s trust.